(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The paper presents the results of a study of sleep hygiene of 120 students receiving higher education and living in dormitories of educational institutions, based on a questionnaire survey. The average age of girls was 19.2 years, boys-19.3 years. We evaluated the duration of nighttime sleep, the presence of daytime sleep, the duration of computer work and mental loads before going to bed, the time of falling asleep and waking up, the time to leave the dorm and the opportunity to have breakfast, the effect of morning exercise and sleep on students ’ well-being, etc. Similarities and differences in sleep hygiene in boys and girls are established. It was found that students living in dormitories have a number of serious sleep problems due to insufficient sleep hygiene.